The Solution Comparison of Time-Fractional Non-Linear Dynamical Systems by Using Different Techniques - Khan, Hassan; Kumam, Poom; Khan, Qasim; Khan, Shahbaz; Hajira,; Arshad, Muhammad; Sitthithakerngkiet, Kanokwan (Frontiers in Physics, 2022)
In this paper, a comparative study of fractional nonlinear fractional Burger,s equations and their systems has been done by using two efficient analytical techniques, The generalized schemes of the proposed techniques for the suggested problems are obtained in a very sophisticated manner. The numerical examples of Burger,s equations and their systems have been solved by using Laplace residual power series method and Elzaki transform decomposition method. The obtained results are compared through graphs and tables. The error tables have been constructed to show the associated accuracy of each method. The procedures of both techniques are simple and attractive and therefore can be extended to solve other important fractional order problems.